The security challenges and Iraqi parliamentary institutions - Albadry, Ammar Saadoon Salman (2014)
More than ten years after the invasion of Iraq by the U.S force, the country is still in total shambles. One major factor to this situation is the lack of security which is considered as an indispensable factor to the political system of Iraq as well as to the effective functioning of the Iraqi parliament.As a result, this study therefore, examined the security challenges and the effective functioning of the Iraqi parliament particularly after the Saddam’s era.It undertakes an in-depth study of face-to-face interview to examine how the security issues affect the Iraqi parliamentary institution functions.The finding revealed that the parliament was unable to effectively discharge their functions due to the security challenges such as terrorism and sectarian violence.